2014
DOI: 10.1007/s11442-015-1156-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of plant species and species-soil relationship in the east central Gurbantunggut Desert, China

Abstract: The distribution of plant species and relationships between species and soil factors in the east central part of Gurbantunggut Desert was studied to provide more insight into the flora and determine differences in vegetation across various parts of the desert. Two-way Cluster Analysis showed that the vegetation in the area could be divided into three groups, the first group was dominated by the shrub species, Ephedra przewalskii and the grass species, Carex physodes mainly in areas of flat grounds and gentle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…, An et al. ). Though there was relatively low biodiversity throughout the entire study area, the variation in the species diversity indices reflected that of the soil characteristics among the eight community types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, An et al. ). Though there was relatively low biodiversity throughout the entire study area, the variation in the species diversity indices reflected that of the soil characteristics among the eight community types.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, variation in the mobilization and accumulation of soil within the desert may result in variation in soil texture across terrains (An et al. ). The results of the present study showed that patterns of species diversity were mainly influenced by soil texture of particle composition properties, which supports the hypothesis that the dominance of shrubs or grasses in semi‐arid grasslands is related to soil texture (Sala et al.…”
Section: Discussionmentioning
confidence: 99%
“…Soil total phosphorus and sand are the dominant factors influencing distribution patterns of desert plants in the Heihe River Basin (Li et al, 2018). Therefore, groundwater, climate, microtopography, and edaphic factors are strong driving forces that sustain ecosystem functions, particularly in arid desert regions (Sommer and Froend, 2014;An et al, 2015;El-Keblawy et al, 2015). Understanding the species distribution and its relationship with environmental factors in arid desert regions will help in planning, managing, and restoring the desert ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The soil physical and chemical properties have a significant influence on plants growth and development (Muenchow et al 2013;Qian et al 2014;An et al 2015), and plants mutually play clear and predictable role in determining the soil nutrient (Fu et al 2015;Novak et al 2017). The soil properties cause heterogeneity over space and time and regulate the vegetation abundance (Silva and Batalha 2008;Brinkmann et al 2009;Otýpková et al 2011;Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In mountainous areas, soil properties (i.e., physical and chemical features) along with topography can play an important role to develop plant communities (Miyamoto et al 2003;Ravanbakhsh and Moshki 2016). According to the previous studies, the soil properties have been introduced as effective factors on variations in species abundance (Marcuzzo et al 2013;Qian et al 2014;Toure et al 2015;An et al 2015;Noumi 2015;Ghaderi et al 2016). Vegetation is one of the most important factors affecting the stability of ecosystems (Ghaderi et al 2016).…”
Section: Introductionmentioning
confidence: 99%